2020
DOI: 10.3390/su12041560
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Urban Park Use and Their Relationship to Factors of Quality: A Case Study of Tehran, Iran

Abstract: Urban parks play an important role in increasing the quality of urban life. Thus, a variety of approaches to planning and decision-making regarding sustainable open spaces and urban parks is needed, especially when models from one location are borrowed to another with a very different culture. In many developing countries cities are expanding without proper planning of public green spaces which places pressure on the quality of life. In common with many Middle Eastern cities, Tehran, the capital of Iran is a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 27 publications
2
48
0
3
Order By: Relevance
“…26,27 A further significant issue for Iranians is that the air quality of Tehran exceeds health recommendations due to motorized vehicle emissions 28 and has been identified as a barrier for participation in physical activity. 29 Solutions such as increasing public transport to reduce vehicle emissions and increase green space for physical activity in Tehran have been implemented through programs such as the Tehran Parks and Green Space Organization 30 but these actions remain a challenge for Tehran city planners.…”
Section: Discussionmentioning
confidence: 99%
“…26,27 A further significant issue for Iranians is that the air quality of Tehran exceeds health recommendations due to motorized vehicle emissions 28 and has been identified as a barrier for participation in physical activity. 29 Solutions such as increasing public transport to reduce vehicle emissions and increase green space for physical activity in Tehran have been implemented through programs such as the Tehran Parks and Green Space Organization 30 but these actions remain a challenge for Tehran city planners.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the MoMRA standard for accessibility fails to provide sufficient coverage of POS in the cities. Regardless of whether these POS are used, policymakers need to adopt a POS typology and create a POS network system to enhance the level of accessibility [ 18 , 29 , 80 , 98 , 99 ].…”
Section: Discussionmentioning
confidence: 99%
“…Urban parks in cities in many developing countries face enormous pressures due to urban sprawl and increasing populations [9]. Tehran, the capital of Iran, suffers from many social and environmental problems and it is not alone among Iranian cities in this respect.…”
Section: Introduction 1the Role and Benefits Of Urban Parks As Urbanmentioning
confidence: 99%
“…Research into preferences for factors affecting park use has been conducted in numerous studies using different methods and has found that aspects such as users' perceptions of security in urban parks [9,32,33] the provision of park facilities [34,35] as well as accessibility [36] are some of the main predictors of satisfaction. Therefore, improved knowledge about different user groups, their cultural situation and needs in interaction with the environment can help improve the function and as a result, parks' environmental balance, stability and sustainability and to make lively spaces with sufficient security [37,38].…”
Section: Introduction 1the Role and Benefits Of Urban Parks As Urbanmentioning
confidence: 99%